Ministérios eclesiais: perspectiva das conferências gerais do episcopado latino-americano e caribenho - Wisniewski, Eliseu; Almeida, Antonio José de (Revista Eclesiástica Brasileira, 2019)
A Igreja desempenha sua missão de evangelizar através da acolhida da vocação ministerial suscitada pelo Espírito Santo. Esta acolhida se expressa em inúmeros serviços voltados para o atendimento de aspectos concretos da vida das comunidades eclesiais. Neste artigo, o Autor tendo presente o Documento Final das Conferências Gerais do Episcopado Latino-americano e Caribenho pretende entender como cada uma delas tratou o tema dos ministérios eclesiais, indicando o percurso feito e assinalando o que considera como conquistas, diferenças e avanços sobre um dos temas mais fundamentais e urgentes para a Igreja. Abstract: The church plays its role to evangelize through the welcome of the ministerial vocation raised by the Holy Spirit. This welcome is expressed in several activities for the care of specific aspects of life of the ecclesial communities. In this article, the author, referring to the Final Document of the General Conference of the Latin American and Caribbean Bishops, intends to understand how each one treated the theme of ecclesial ministries, indicating the way and showing what he considers as achievements, differences and advances on one of the most fundamental and urgent role for the Church Keywords: Latin American Episcopate; General Conferences; Latin American Church; Ordained ministries; Non-ordained ministries.